Provision of key accessibility issues (KAIs) for people with disabilities in public transportation hub towards social sustainability / Nur Ainaa Azmi - Azmi, Nur Ainaa (2022)
Electric Train Services station is one of the important public transport stations as it connects the surrounding communities with their social life. Thus, the station shall be made accessible to its users, particularly people with disabilities (PwDs). The MS1184:2014 had outlined a set of key accessibility issue (KAIs) to be fulfilled by all public places to ensure that the services and facilities provided are convenient to the PwDs. However, many researchers reported that the public transportation hub in Malaysia are still lacking in providing an accessible facility to the PwDs. Many of the facilities and services provided at the station do not comply with the Malaysian Standard (MS). Recently, many PwDs has been taking part in economic activity in many major cities in Malaysia. Most of them prefer to use trains or buses as their mode of transportation because it is cheaper than taxi or driving. However, due to barriers to the trains or bus stations, PwDs had difficulties commuting to their workplace or travelling to other places. This research aims to investigate whether the KAIs for PwDs provided at the ETS station comply with social sustainability (SOCSAS) elements. Three research objectives were established (1) to identify the elements of social sustainability to be provided for PwDs, (2) to explore the compliance of KAIs for PwDs provided at the ETS stations with the Malaysian Standard and (3) to evaluate whether the provision of KAIs for PwDs provided at the ETS stations contributes towards SOCSAS elements. Three ETS stations were chosen as the case study and a purely qualitative methods were employed. The method used to obtain data were document analysis, observations and semi-structured interviews with three respondents. To assist the observation process, an observation checklist was developed by conducting document analysis on the MS1184:2014. The semi-structured interview data were analysed using Atlas.ti8. The findings observed that although majority of the dimension of KAIs for PwDs are provided at the ETS stations but some of the dimensions were in compliance with the MS. These incompliances affect the social sustainability (SOCSAS) of PwDs and makes them feel excluded from the society. Therefore, it is hoped the research findings will create the awareness among the construction team on the importance of the accessibility of PwDs at the stations. Notwithstanding, this research also helps in achieving the SDGs (Goal 11) in future by providing a better environment for all by having a sustainable transport.